Russia and its Army in the Crimean War of 1853-1856 through the Eyes of Karl Marx and Friedrich Engels - Sergey Yuryevich Chimarov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article contains analysis of Karl Mar and Friedrich Engels opinion on the reasons of appearance the “Eastern Question”, the moments of interfaith between Russian Orthodoxies and Turkish EmpireMuslims, analysis of Russian role in a Global problem solving process in the middle of XIX century and its level of economic and civilization development. The author appeal to the Marxist negative position toward Russia - its culture, nation, army and position, which one was veiled by revolutionary appeals and democracy reasoning.